Developing stratified epithelia: lessons from the epidermis and thymus. (29th August 2014) - Roberts, Natalie; Horsley, Valerie
<x xml:space="preserve">Abstract</x> Stratified squamous epithelial cells are found in a number of organs, including the skin epidermis and the thymus. The progenitor cells of the developing epidermis form a multi‐layered epithelium and appendages, like the hair follicle, to generate an essential barrier to protect against water loss and invasion of foreign pathogens. In contrast, the thymic epithelium forms a three‐dimensional mesh of keratinocytes that are essential for positive and negative selection of self‐restricted T cells. While these distinct stratified epithelial tissues derive from distinct embryonic germ layers, both tissues instruct immunity, and the epithelial differentiation programs and molecular mechanisms that control their development are remarkably similar. In this review, we aim to highlight some of the similarities between the thymus and the skin epidermis and its appendages during developmental specification. WIREs Dev Biol 2014, 3:389–402. doi: 10.1002/wdev.146 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.